(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Most people and students experience stress and anxiety from time to time. Stress is any demand placed on your brain or physical body. People and students can report feeling “stressed” when multiple competing demands are placed on them. The feeling of being “stressed” can be triggered by an event that makes you feel frustrated or nervous. According to recent studies the average age of onset for many mental health conditions is the typical college age range of 18 to 24 years old, said Courtney Knowles, in fact, according to the National Institute of Mental Health, 75 percent of all individuals with an anxiety disorder will experience symptoms before age 22, as cited. The study aimed to find the Effectiveness of the self-instructional module on knowledge regarding the effect of outdoor games on stress and anxiety reduction among adolescents at selected high schools in the Gwalior District. MethodologyAn evaluative approach with a pre-experimental one-group pre-test post-test design was used with a simple random sampling technique to select the sample (N=60). A structured knowledge questionnaire was used to assess the knowledge and SIM was administered to find its effectiveness. The collected data were analyzed by using descriptive & inferential statistics. Results-The mean percentage of post-test knowledge score (81.20%) was higher than the mean percentage of pre-test knowledge score (49.70%). The calculated ‘t’ value is greater than the table value (0.05, 59df) = 2.00. It shows a significant difference between mean pre and post-test knowledge scores. (Calculated x2 values are shown). There was a significant association formed between the type of the family, residential area, and source of information respondents with their pre-test knowledge scores.Conclusion: The finding of the study shows a deficit in knowledge of adolescents before the administration of SIM. The results indicated that the SIM was effective in increasing the knowledge of adolescents on the effect of outdoor games on stress and anxietyreduction.